2019
DOI: 10.1103/physrevapplied.11.054004
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Pump Driven by Anisotropic Phoresis

Abstract: Fluid flow along microchannels can be induced by keeping opposite walls at different temperatures, and placing elongated tilted pillars inside the channel. The driving force for this fluid motion arises from the anisotropic thermophoretic effect of the elongated pillars that generates a force parallel to the walls, and perpendicular to the temperature gradient. The force is not determined by the thermophilic or thermophobic character of the obstacle surface, but by the geometry and the thermophoretic anisotrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…microfilaments/microtubules self-organizing in the cytoplasm, immune cells migrating in tissue, bacterial locomotion in soil, and application of selfpropelled particles in microfluidic devices, drug delivery or other biomedical operations. 1,[30][31][32][33][34] Hence, much research effort has been devoted to investigating the behavior of active objects in contact with obstacles. It is found that an active agent can be captured and trapped around a circular obstacle depending on the propelling mechanism and/or hydrodynamic or other alignment interactions.…”
Section: Introductionmentioning
confidence: 99%
“…microfilaments/microtubules self-organizing in the cytoplasm, immune cells migrating in tissue, bacterial locomotion in soil, and application of selfpropelled particles in microfluidic devices, drug delivery or other biomedical operations. 1,[30][31][32][33][34] Hence, much research effort has been devoted to investigating the behavior of active objects in contact with obstacles. It is found that an active agent can be captured and trapped around a circular obstacle depending on the propelling mechanism and/or hydrodynamic or other alignment interactions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, the multiparticle collision dynamics (MPC) method, a particle-based hydrodynamic simulation approach which captures hydrodynamic interactions and thermal fluctuations, [11][12][13][14][15][16][17] has been proven valuable and efficient for mesoscale simulations, and has been applied in a broad range of studies of biological and active polymers, [18][19][20][21][22][23][24][25][26] colloids, [27][28][29][30][31] proteins, 32,33 vesicles and blood cells, 34,35 microswimmers, [36][37][38][39][40][41][42][43][44][45][46] and microfluidics. 47,48 To date, various MPC implementations of binary fluid mixtures have been proposed, and their phase behavior has been studied. [49][50][51][52][53][54][55]…”
Section: Introductionmentioning
confidence: 99%
“…Dissipative particle dynamics (DPD) simulations, which explicitly account of conservative pair interactions between fluid particles, allow to realize multi-phase fluids via assigning distinct interactions between the particles [10]. Furthermore, the multiparticle collision dynamics (MPC) method, a particlebased hydrodynamic simulation approach which captures hydrodynamic interactions and thermal fluctuations [11][12][13][14][15][16][17], has been proven valuable and efficient for mesoscale simulations, and has been applied in a broad range of studies of biological and active polymers [18][19][20][21][22][23][24][25][26], colloids [27][28][29][30][31], proteins [32,33], vesicles and blood cells [34,35], microswimmers [36][37][38][39][40][41][42][43][44][45][46], and microfluidics [47,48]. To date, various MPC implementations of binary fluid mixtures have been proposed, and their phase behavior has * z.tan@fz-juelich.de been studied [49][50][51][52]…”
Section: Introductionmentioning
confidence: 99%